Effect of organic chromium (chromium picolinate) supplementation on production parameters, egg quality attributes and serum biochemistry in Pearl guinea fowls during second laying cycle - GOPI, M; PRABAKAR, G; KOLLURI, G; TAMILMANI, T; TYAGI, J S; MOHAN, JAG (The Indian Journal of Animal Sciences, 2018)
A biological experiment was carried out with adult Pearl guinea fowl variety (160) in second laying cycle to assess the performance, hemato-biochemical attributes, egg quality and stress levels. Each treatment consisted of four replicates with ten birds in each replicate. The birds were reared for 42 days under battery cage system and fed with ad lib. feed and water. The experiment groups were control group fed basal diet without any supplementation of chromium picolinate (CrP), T1 fed basal diet with 500 ppb CrP, T2 fed basal diet with 1,000 ppb CrP and T3 fed basal diet with 1,500 ppb CrP. There was no significant change in body weight and feed intake due to supplementation of CrP. However, supplementation of CrP significantly reduced the erythrocytes osmotic fragility (%), serum glucose, total cholesterol and improved the egg internal and external quality traits. The supplementation of CrP significantly improved both the internal and external egg quality along with shell thickness. From this study, it can be concluded that supplementation of chromium as chromium picolinate @ 500 ppb improved the egg qualityÂ  and reduced the stress in Pearl guinea fowl during second laying cycle.